The impact of perceived quality on assisted living residents’ satisfaction with their dining experience - Howells, Amber D. (Kansas State University, 2007)
The purposes of this study were to explore factors associated with residents’ dining experience in assisted living facilities and to investigate the influence that these factors had on perceived quality and residents’ satisfaction with their dining experience. Food quality, service quality, mealtime customization, and dining room environment were the four constructs explored. Focus groups were conducted with residents of three assisted living facilities to determine attributes of the constructs that were important to them. A total of 22 residents participated in the three focus groups. A questionnaire developed by Huang was revised to include measurement items identified in the focus groups. The questionnaire was distributed to residents of 16 randomly selected assisted living facilities within a 110 mile radius of the research institution. Of the 492 residents in 16 facilities, 246 completed the questionnaire for a response rate of 50%. Residents evaluated the attributes on a 5-point likert scale (1-strongly disagree; 5-strongly agree). Service quality (4.03) and dining room environment (3.97) attributes were rated significantly higher than food quality (3.64) and customization attributes (3.42). Resident satisfaction also was evaluated on a 5-point scale (1-very dissatisfied; 5-very satisfied). Residents were satisfied with the overall dining experience (3.94) and the overall facility (3.97). Residents were less satisfied with food served (3.67) or the amount of choices they had at meals (3.58). Residents were satisfied with services (3.95) and the dining room atmosphere (3.98). Satisfaction with services and the dining room atmosphere were significantly higher than food served and amount of choices at mealtimes. Residents’ perceptions of food quality, service quality, level of customization, and dining room environment had a positive influence on their satisfaction with the overall dining experience. Residents’ perceptions of food quality had a positive influence on satisfaction with the food served, service quality impacted satisfaction with services, level of customization effected satisfaction with the amount of choices, and dining room environment influenced satisfaction with the dining room atmosphere. Administrators, foodservice directors, and dietitians employed in assisted living facilities can use the results to improve the dining experience for residents and ultimately improve residents’ quality of life.
Keywords: Foodservice; Dining experience; Elderly; Long-term care; Assisted living facility; Gerontology (0351); Health Sciences, Nutrition (0570)